Petroleum Prices in Bangladesh : A Need for Regular and Appropriate Adjustments - World Bank (Washington, DC, 2012)
Under-pricing of diesel and kerosene continues to cause major financial problems for Bangladesh Petroleum Corporation (BPC), which is losing over Tk 2 billion monthly. Global forecasts suggest that oil prices will continue to be over $US 50 per barrel for the next couple of years. Bangladesh's Household Income and Expenditure Survey data for 2005 indicate that both diesel and kerosene form a very small part of the budget of the poor. One option, therefore, is to raise the price of diesel and kerosene from current Tk 33 to 41 per liter and make BPC breakeven on its trading costs. BPC's trading cost is roughly 70 percent of its total current costs; the latter includes an ever increasing interest bill, currently at Tk 4.7 billion. If the one step increase is considered difficult, a second option would be to phase the increase over a six-month period with each increase of Tk 4 per liter, possibly in sync with the 'boro' rice planting season. A major communication campaign should be launched to inform the public the rationale of the price increase. Future adjustments should be based on a formula that automatically adjusts prices-both upwards and downwards, on a regular basis.